Relevant coexpression of STMN1, MELK and FOXM1 in glioblastoma and review of the impact of STMN1 in cancer biology - Serachi,Fernanda de Oliveira (2017)
OBJECTIVE: To analyze the associated expression of STMN1, MELK and FOXM1 in search of alternative drugable target in glioblastoma (GBM) and to review relevant functional roles of STMN1 in cancer biology. METHOD: STMN1, MELK and FOXM1 expressions were studied by quantitative PCR and their coexpressions were analyzed in two independent glioblastoma cohorts. A review of articles in indexed journals that addressed the multiple functional aspects of STMN1 was conducted, focusing on the most recent reports discussing its role in cancer, in chemoresistance and in upstream pathways involving MELK and FOXM1. RESULTS: Significant associated expressions of MELK and FOXM1 were observed with STMN1 in GBM. Additionally, the literature review highlighted the relevance of STMN1 in cancer progression. CONCLUSION: STMN1 is very important to induce events in cancer development and progression, as cellular proliferation, migration, and drug resistance. Therefore, STMN1 can be an important therapeutic target for a large number of human cancers. In glioblastoma, the most aggressive brain tumor, the MELK/FOXM1/STMN1 presented significant associated expressions, thus pointing MELK and FOXM1 as alternative targets for therapy instead of STMN1, which is highly expressed in normal brain tissue. Continuous functional research to understand the STMN1 signaling pathway is worthwhile to improve the therapeutic approaches in cancer.